1987
DOI: 10.1136/adc.62.7.712
|View full text |Cite
|
Sign up to set email alerts
|

Severe pre-eclampsia and infants of very low birth weight.

Abstract: SUMMARY The effect of severe pre-eclampsia on the outcome of infants of very low birth weight was studied in a prospective case control study of 35 pairs of infants of comparable gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
3
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 19 publications
4
44
3
2
Order By: Relevance
“…Previous studies evaluating the effects of preeclampsia on newborn infants have focused on the incidence of prematurity (21), intrauterine growth retardation (22), neonatal mortality (2), and hematological changes such as neutropenia (6) and thrombocytopenia (7). Little attention has been given to potential hemodynamic effects of preeclampsia in the neonate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluating the effects of preeclampsia on newborn infants have focused on the incidence of prematurity (21), intrauterine growth retardation (22), neonatal mortality (2), and hematological changes such as neutropenia (6) and thrombocytopenia (7). Little attention has been given to potential hemodynamic effects of preeclampsia in the neonate.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have suggested that severe maternal preeclampsia is associated with a high incidence of neonatal hypotension. 19,20 Those studies did not exclude the possibility that the increased incidence of neonatal hypotension in infants born to mother with preeclampsia might have resulted from lower birth weight or fetal exposure to magnesium sulfate. Nonetheless, preeclampsia is an attractive primary etiology of neonatal hypotension as preeclampsia tends to cause intrauterine growth retardation and to result in fetal exposure to magnesium sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…10 Other investigators have linked neonatal hypotension to an increased risk of central nervous system morbidities, such as intraventricular hemorrhage, 11,12 white matter injury, 13 poor neurodevelopmental outcome 14,15 and threshold retinopathy of prematurity. 16 The etiology of neonatal hypotension is likely multifactorial, 17,18 but recently severe preeclampsia 19,20 has been suggested to be a contributing factor. These studies did not define the diagnostic criteria for neonatal hypotension, nor the age of diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, Szymonowicz y cols., encontraron mayor frecuencia de dificultad respiratoria en los recién nacidos de muy bajo peso al nacer hijos de madres con PE; 40 Habli y cols., encontraron esta misma asociación en recién nacidos cercanos al término, 41 mientras que Friedman y cols., no hallaron diferencias entre los RN de madre preeclámpticas y madres normotensas; 42 a su vez, Shah et al describen menor frecuencia de SDR en RN pretérminos de madres con PE. 32 Otro estudio que contribuye a esta contradicción es la cohorte histórica de los partos de entre 24 y 37 semanas atendidos entre 1996 y 2002 en la Universidad Médica de Carolina del Sur que Chang y cols.…”
Section: Síndrome De Dificultad Respiratoriaunclassified
“…32 Por otro lado, aunque no hay estudios de cohorte sino de casos y controles, en relación con leucomalacia periventricular y PE el fenómeno es el mismo: Hatzidaki y cols. encontraron mayor frecuencia de leucomalacia periventricular en neonatos expuestos a PE, 49 mientras que Szymonowicz 40 o Murata, 50 no pudieron establecer que la PE fuera factor de riesgo para desarrollar esta entidad.…”
Section: Problemas Del Sistema Nervioso Centralunclassified